Determining the severity of obstructive sleep apnea (OSA) by using numerical analysis / Ang Ming Lok - Ang , Ming Lok (2020)
Computational technologies and biomechanical theories have been applied to study upper airway mechanics in obstructive sleep apnea (OSA). In this study, the patient is selected from ENT Department, UMMC, diagnosed with mild to severe OSA. In addition, the patient underwent maxillomandibular advancement (MMA) surgical treatment. Therefore, 3-dimensional modeling software will be used to model the upper airway, based on patient specific geometrical characteristics obtained from medical imaging and computed tomography (CT). Hence, providing an accurate assessment of airflow characteristics. Computational fluid dynamics (CFD) analysis will be combined with upper airway geometries obtained before and after surgical to determine the effects on parameters, such as, pressure drop and turbulent kinetic energy. Moreover, Patient-specific airway geometries obtained from CT scans is used to determine treatment therapy for OSA syndrome. CFD is therefore an attractive method to model treatment outcome in OSA patient-specific airway geometry before implementation of treatment devices or performing surgery.